Susceptibility of some oral microorganisms to chlorhexidine and paramonochlorophenol Susceptibilidade de alguns microrganismos orais frente à clorexidina e ao paramonoclorofenol - Crystiane Venditi Gomes do Amorim; Carlos Eduardo Aun; Marcia Pinto Alves Mayer (Sociedade Brasileira de Pesquisa Odontológica, 2004)
Since the use of antimicrobial agents is required in endodontic therapies, this study aimed at determining the minimum inhibitory concentrations (MICs) of chlorhexidine digluconate and paramonochlorophenol (PMC) against microorganisms commonly found in endodontic infections. Both agents were tested by agar dilution tests against Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Candida albicans, Prevotella intermedia, Porphyromonas gingivalis, Porphyromonas endodontalis, Prevotella denticola and Prevotella melaninogenica. The MIC of chlorhexidine ranged from 2.67 to 80.00 µg/ml, and the MIC of PMC from 46.67 to 213.33 µg/ml. The highest MIC value of PMC was detected for E. faecalis whereas E. coli was the most susceptible microorganism to this agent. The highest MIC values of chlorhexidine were observed for P. aeruginosa whereas E. coli and P. denticola were the most susceptible microorganisms to this agent. Since the MIC values observed are much lower than the concentrations currently used in the endodontic therapy, it is suggested that both agents are effective in reducing the microbiota in the root canal. Tendo em vista a necessidade de se utilizarem agentes antimicrobianos durante a terapia endodôntica, o presente estudo tem por objetivo determinar as concentrações inibitórias mínimas (CIMs) de digluconato de clorexidina e de paramonoclorofenol (PMC) frente a cepas de microrganismos freqüentemente isolados dos canais radiculares infectados. Ambos os agentes foram testados por meio de testes de diluição em meio sólido contra Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Candida albicans, Prevotella intermedia, Porphyromonas gingivalis, Porphyromonas endodontalis, Prevotella denticola e Prevotella melaninogenica. As CIMs de clorexidina variaram de 2,67 a 80,00 µg/ml, e as CIMs de PMC variaram de 46,67 a 213,33 µg/ml. A maior CIM do paramonoclorofenol foi frente a E. faecalis, entretanto E. coli foi o microrganismo mais susceptível. A maior CIM do digluconato de clorexidina foi frente a P. aeruginosa, entretanto E. coli e P. denticola foram os microrganismos mais susceptíveis. Como os valores de CIM observados são bem menores do que as concentrações usadas normalmente na terapia endodôntica, sugere-se que ambos os agentes são efetivos na redução microbiana no canal radicular.